Primary stability of cement augmentation in locking plate fixation for proximal humeral fractures: A comparison of absorbable versus non-absorbable cement. (January 2022) - Schöbel, Tobias; Schleifenbaum, Stefan; Nitsch, Viktoria; Hepp, Pierre; Theopold, Jan
Abstract: Background: Cement augmentation has been suggested to increase the stability of screw anchoring in osteoporotic humeral fractures. Initial results are promising but may be jeopardized by cement leakage into the joint and difficult implant removal. Absorbable cement might have advantages in this regard, but it is unclear if the primary stability of both techniques is equivalent to each other. Therefore, this study aimed to compare its primary stability with that of non-absorbable cement augmentation. Methods: Nineteen cadaveric humeri with two-part fracture models were treated with locking plate osteosynthesis and cement augmentation using either absorbable calcium phosphate cement (group 1) or polymethylmethacrylate (group 2). Fracture movement, stiffness, failure mode, and ultimate load under cyclic compressive loading were examined and compared between the groups. Findings: The absolute and relative stiffness values in group 1 were significantly smaller than those in group 2 after 50 cycles (group 1: 114 ± 38 N/mm and 94 ± 8% vs. group 2: 188 ± 71 N/mm and 106 ± 9%; p50 = 0.022), 2000 cycles (group 1: 97 ± 34 N/mm and 81 ± 15% vs. group 2: 153 ± 47 N/mm and 88 ± 15%; p2000 = 0.028), and 5000 cycles (group 1: 98 ± 40 N/mm and 81 ± 22% vs. group 2: 158 ± 40 N/mm and 92 ± 16%; p5000 = 0.028). The failure load was not statistically significantly different between the groups. Interpretation: Although the PMAA group showed higher values for absolute and relative stiffness, no statistically significant difference was found in the primary stability between absorbable and non-absorbable cement augmentation supporting plate osteosynthesis in proximal humeral fractures. In view of the potential advantages of bio-absorbable cement during the healing process, its use should be considered for the augmentation and stabilization of osteoporotic fractures. Highlights: Stable fixation of osteoporotic proximal humeral fractures remains a challenge. Cement augmentation improves insufficient screw anchoring in locked plating. Cyclic loading showed good primary stability of resorbable cement in this study. Use of resorbable cement may facilitate healing and reduce complications. Clinical confirmation of improved healing is required.